A REVIEW OF LITERATURE ON THE EVALUATION OF CUSTOMER SATISFACTION PATTERNS IN MOBILE BANKING SERVICES [UMA REVISO DA LITERATURA SOBRE A AVALIAO DOS PADRES DE SATISFAO DO CLIENTE EM SERVIOS BANCRIOS MVEIS] [UNA REVISIN DE LA LITERATURA SOBRE LA EVALUACIN DE LOS PATRONES DE SATISFACCIN DEL CLIENTE EN LOS SERVICIOS DE BANCA MVIL] - Khadim N. (AOS-Estratagia and Inovacao, 2023)
Purpose: Providing high-quality e-banking services and trust is considered a basic strategy for attracting and retaining customers with mobile banking that is less investigated particularly in Iraq. A review of the literature was conducted to achieve these goals. Theoretical framework: The scarcity of literature in terms of mobile banking in Iraqi setting was the theoretical basis of the current study. Previous related research was collected and reviewed thematically to understand the trends of the latest literature in mobile banking and customer satisfaction. Design/methodology/approach: A narrative approach was utilized in the context of this study. Several studies published between 2016 and 2022 were reviewed. Through this semi systematic literature review different key words were keyed in numerous e-journal database. Findings: the review revealed that most of the studies in this article utilized qualitative approach as an appropriate method to elicit data. The participants were from ordinary people one study investigated the variables of mobile banking and customer satisfaction among bank staff. Service quality was the highest variable compare with security and ease of use. The review indicated also there a limitation in the previous studies in the Iraqi mobile banking setting. Research, Practical & Social implications: Mobile banking as an emerging research area specially in Iraqi environment needs more investigation since such kind of research could increase people awareness about the advantage of such technology in the banking industry. Originality/value: Even though mobile banking is not a novel concept in Iraq, there is no literature that discusses the use of service quality modal to evaluate a user's level of satisfaction in the mobile banking research area. As a result, the purpose of this paper is to make up for this void. 2022 Intern. Journal of Profess. Bus. Review. All rights reserved.